The Relationship between Obesity and Anemia among Adolescent Girls - Muhammad Nur Hasan Syah (Poltekkes Kemenkes Palu, 2022)
Nutrition problems that are often faced by adolescent are obesity and anemia. Obesity in adolescent increases the risk of anemia due to inflammation. Inflammation that occurs in obese adolescent will cause disruption of iron absorption and a decrease in hemoglobin levels. This research aims to determine the relationship of obesity with the occurrence of anemia in adolescent in SMK of Bekasi City. This type of research is observational analytic with cross sectional method. The independent variable in this research is obesity and the dependent variable is the occurrence of anemia. The subjects of the research are adolescent of SMK of Bekasi City who met the inclusion and exclusion criteria. The data obtained were statistically analyzed by chi-square test. The results of this research indicate 19.5% of adolescent have a status nutrition overweight and obesity and 31.4% of adolescent experiencing anemia. Adolescent are anemic obesity amounted to 12.5% and shows there is a connection between obesity with the incidence of anemia in adolescent in SMK Kota Bekasi (p < 0.05). The conclusions of the research are obesity can increase the risk of anemia in adolescent